New Cannibal Markets : Globalization and Commodification of the Human Body - Jean-Daniel Rainhorn (Éditions de la Maison des sciences de l'homme, 2015)
Thanks to recent progress in biotechnology, surrogacy, transplantation of organs and tissues, blood products or stem-cell and gamete banks are now widely used throughout the world. These techniques improve the health and well-being of some human beings using products or functions that come from the body of others. Growth in demand and absence of an appropriate international legal framework have led to the development of a lucrative global trade in which victims are often people living in insecure conditions who have no other ways to survive than to rent or sell part of their body. This growing market, in which parts of the human body are bought and sold with little respect for the human person, displays a kind of dehumanization that looks like a new form of slavery. This book is the result of a collective and multidisciplinary reflection organized by a group of international researchers working in the field of medicine and social sciences. It helps better understand how the emergence of new health industries may contribute to the development of a global medical tourism. It opens new avenues for reflection on technologies that are based on appropriation of parts of the body of others for health purposes, a type of practice that can be metaphorically compared to cannibalism. Are these the fi rst steps towards a proletariat of men- and women-objects considered as a reservoir of products of human origin needed to improve the health or well-being of the better-off? The book raises the issue of the uncontrolled use of medical advances that can sometimes reach the anticipations of dystopian literature and science fiction.